Algorithms for Decision Making - Kochenderfer, Mykel J., 1980-; Wheeler, Tim A. (Tim Allan); Wray, Kyle H. (Cambridge, Massachusetts : The MIT Press, 2022)
"This text introduces decision making under uncertainty from a computational perspective and provides an overview of the methods for building autonomous and decision-support systems"--
Includes bibliographical references (pages 651-669) and index.
Keywords: Decision support systems -- Mathematics; Algorithms